PERAN AGROFORESTRI KARET TERHADAP PENDAPATAN PETANI KARET DI DESA MABURAI PROVINSI KALIMANTAN SELATAN - Adi Saputra; Daniel Itta; Asysyifa - (Lambung Mangkurat University-Indonesia, 2021)
The research location is in Maburai Village, Murung Pudak District, Tabalong Regency, South Kalimantan Province, rubber land that uses the rubber agroforestry system as the object of research. The purpose of this study was to analyze the role of rubber agroforestry in order to increase the income of rubber farmers. The method used in this study to find respondents is by using the Accidental Sampling method. Based on the results of the research that has been carried out, the role of rubber agroforestry is divided into 2 parts, namely, rubber plants for sale, and intercrops play a role for sale, self-consumption, and taken by land owners. The contribution from intercropping was only 4 people who sold the intercrops in the form of fruit, the largest income from the intercropping was Rp. 12,000,000 with a percentage of 19% of the total income of Rp. 63,200,000. There are two factors that affect the agroforestry system, namely internal factors based on farmers' experience, motivation to carry out the rubber agroforestry system, land area, number of plants other than rubber, and types of plants other than rubber, while external factors are the absence of support by rubber agro-forestry extension agencies in Maburai Village, and community leaders.